GAE and OBE Enhanced Interference Mitigation Techniques in LDACS - Miziya Keshkar; Raja Muthalagu; Abdul Rajak; Libin K. Mathew (Aerospace, 2022)
Interference mitigation in L-band digital aeronautic communication systems from legacy users is vital due to stringent safety requirements and steady-state increase in air traffic. This paper proposes an L-band digital aeronautic communication systems receiver prototype that employs nonlinear operations to reduce the interference from the prime interference contributor distance measuring equipment. The knowledge of genie-aided estimator and optimum Bayesian estimator is utilized to propose improved and low complexity nonlinear devices, such as a genie-aided estimator enhanced pulse peak attenuator, genie-aided estimator enhanced pulse peak limiter, joint genie-aided estimator enhanced pulse peak attenuator, joint genie-aided estimator enhanced pulse peak limiter, optimum Bayesian estimator enhanced pulse peak attenuator, optimum Bayesian estimator enhanced pulse peak limiter, joint optimum Bayesian estimator enhanced pulse peak attenuator and joint optimum Bayesian estimator enhanced pulse peak limiter. The performance of the proposed methods is compared with the classical pulse blanking in terms of the received bit error rate for different signal-to-noise ratios. The proposed genie-aided estimator enhanced methods exhibited SNR saving in the range of 2 to 2.5 dB at a bit error rate of <semantics>10−1</semantics>. At the same BER, the proposed optimum Bayesian estimator enhanced methods achieved SNR saving in the range of 2.5 to 3 dB.